PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) TERHADAP KEMANDIRIAN BELAJAR SISWA DALAM MATA PELAJARAN PPKN DI KELAS VII - Ocarina, Estika; Japar, Muhammad; Yasin, Yasnita; Fadfhillah, Dini Nur (Program Studi IPS Universitas Negeri Semarang Kampus Sekaran, Gunungpati, Semarang, 2019)
This study aims to determine the independence of learning in the civic education area in class VII at 92 Junior High School between before the implementation of group investigation (GI) learning model after the implementation of group investigation (GI) learning model. This research uses experimental method. This experimental study used the Pretest-Posttest Control Design design. The design consists of two groups, namely the experimental group and the control group. Both groups were given pre and post test but only one group was given treatment (treatment). With this design, there are differences in the achievement of independence between the experimental group and the achievement of the independence of the control group. Data collection uses questionnaires to collect data on learning independence. The population of this study are all students of class VII at 92 Junior High School from class VII A to class VII F. While technique used for this research use Simple Random Sampling with obtained class VII F as experiment class and class VII C as control class. The study was conducted from early March 2017 to early May 2017. The data collected were analyzed using statistical analysis technique. Testing the research hypothesis using T-test. Hypothesis testing showed that: 1) The sample of the experimental class and the control class came from the normally distributed population. 2) Based on the data analysis both samples are homogeneous; 3) There is a higher change in terms of learning independence in the class that received treatment compared with the class that did not receive treatment. The conclusion of this research there is a higher influence of the use of group investigation model (GI) of student independence learning in the civic education at 92 Junior High School Jakarta.   Penelitian ini bertujuan untuk mengetahui kemandirian belajar di bidang pendidikan kewarganegaraan di kelas VII di 92 SMP antara sebelum penerapan model pembelajaran investigasi kelompok (GI) setelah penerapan model pembelajaran investigasi kelompok (GI). Penelitian ini menggunakan metode eksperimen. Penelitian eksperimental ini menggunakan desain Desain Kontrol Pretest-Posttest. Desain terdiri dari dua kelompok, yaitu kelompok eksperimen dan kelompok kontrol. Kedua kelompok diberikan pre dan post test tetapi hanya satu kelompok yang diberi perlakuan (treatment). Dengan desain ini, ada perbedaan dalam pencapaian kemandirian antara kelompok eksperimen dan pencapaian kemandirian kelompok kontrol. Pengumpulan data menggunakan kuesioner untuk mengumpulkan data tentang kemandirian belajar. Populasi penelitian ini adalah semua siswa kelas VII SMP Negeri 92 dari kelas VII A sampai kelas VII F. Sedangkan teknik yang digunakan untuk penelitian ini menggunakan Simple Random Sampling dengan diperoleh kelas VII F sebagai kelas eksperimen dan kelas VII C sebagai kelas kontrol . Penelitian dilakukan dari awal Maret 2017 hingga awal Mei 2017. Data yang dikumpulkan dianalisis dengan menggunakan teknik analisis statistik. Pengujian hipotesis penelitian menggunakan uji-T. Pengujian hipotesis menunjukkan bahwa: 1) Sampel kelas eksperimen dan kelas kontrol berasal dari populasi yang berdistribusi normal. 2) Berdasarkan analisis data, kedua sampel homogen; 3) Ada perubahan yang lebih tinggi dalam hal kemandirian belajar di kelas yang menerima pengobatan dibandingkan dengan kelas yang tidak menerima pengobatan. Kesimpulan dari penelitian ini ada pengaruh yang lebih tinggi dari penggunaan model investigasi kelompok (GI) pembelajaran kemandirian siswa dalam pendidikan kewarganegaraan di 92 SMP Jakarta